PEMBELAJARAN AKUNTANSI PERUSAHAAN JASA BAGI SISWA KELAS 11 - Dewi, Syanti; Lestari , Levina; Pratama, Go Cecilia Claudia (Jurnal Serina Abdimas, 2024)
Continuous practice allows students to systematically engage themselves in an iterative learning process, where they not only understand accounting material theoretically, but apply it in real financial situations. Along with this, it is also important to pay attention to the development of students' problem-solving skills in a financial context. Students not only face a variety of simple financial situations, but also increasing complexity as they progress. This allows them to face greater challenges and learn to design effective strategies in solving complex financial problems. Through a continuous approach to accounting learning, students not only hone their analytical skills, but also deepen their understanding of the importance of financial information in the decision-making process. This not only involves understanding the accounting of service companies, but also manufacturing companies, and other sectors. This activity, carried out at a high school in Jakarta, allows students to see accounting concepts applied differently in various industrial contexts, enriching their understanding of the complexities of the business world as a whole. The results of the learning are held face to face accompanied by practice questions, questions and answers and quizzes. This has the positive impact of providing students with a strong foundation in accounting, and also preparing them to become critical thinkers, skilled problem solvers, and competent leaders in the ever-evolving business world. All of this is felt after they graduate, not only academically successful, but becoming professionals who are ready to face the challenges of the world of work with confidence and adequate skills. ABSTRAK Latihan yang berkelanjutan memungkinkan siswa untuk secara sistematis melibatkan diri dalam proses belajar yang iteratif, di mana mereka tidak hanya memahami materi akuntansi secara teoritis, tetapi menerapkannya dalam situasi keuangan yang nyata. Seiring dengan itu, penting juga untuk memperhatikan pengembangan keterampilan pemecahan masalah siswa dalam konteks keuangan. Siswa tidak hanya menghadapi berbagai situasi keuangan yang sederhana, tetapi juga kompleksitas yang semakin meningkat seiring dengan kemajuan mereka. Ini memungkinkan mereka untuk menghadapi tantangan yang lebih besar dan belajar merancang strategi yang efektif dalam menyelesaikan masalah-masalah keuangan yang rumit. Melalui pendekatan yang terus-menerus dalam pembelajaran akuntansi, siswa tidak hanya mengasah kemampuan analitis mereka, tetapi juga memperdalam pemahaman mereka tentang pentingnya informasi keuangan dalam proses pengambilan keputusan. Ini tidak hanya melibatkan pemahaman tentang akuntansi perusahaan jasa, tetapi juga perusahaan manufaktur, dan sektor lainnya. Kegiatan ini, dilakukan di sekolah menengah atas di Jakarta, sehingga siswa dapat melihat konsep akuntansi diterapkan secara berbeda dalam berbagai konteks industri, memperkaya pemahaman mereka tentang kompleksitas dunia bisnis secara keseluruhan. Hasil dari pembelajaran, diadakan secara tatap muka disertai dengan latihan soal, tanya jawab dan kuis. Hal ini membawa dampak yang bagus agar memberikan dasar yang kuat dalam akuntansi kepada peserta didik, dan juga mempersiapkan mereka untuk menjadi pemikir kritis, pemecah masalah yang terampil, dan pemimpin yang kompeten dalam dunia bisnis yang terus berkembang. Semua ini dirasakan setelah mereka lulus, tidak hanya sukses secara akademis, tetapi menjadi profesional yang siap menghadapi tantangan dunia kerja dengan percaya diri serta keterampilan yang memadai.